Vybrané části stavebně technologického projektu železobetonového mostu v obci Mostkovice - Procházka, Miroslav (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Diplomová práce se zabývá vybranými částmi STP železobetonového mostu v obci Mostkovice. Jedná se o nahrazení stávající zděné konstrukce novým, železobetonový rámem plošně založeným. Součástí práce jsou kromě jiného časový a finanční plán, rozpočet a situace stavby, zařízení staveniště, studie realizace, nasazení hlavních mechanismů, BOZP a technologický předpis.

This thesis deals with selected Parts of the construction technology project of reinforced concrete bridge in Mostkovice. It is about a replacement of the existing masonry construction of new, reinforced-concrete frame founded on surface. Part of the work in addition to other are schedule and financial plan, budget and construction situation, site equipment, study of realization, plan of using the main mechanisms, health and safety at work and technological prescription.
Selected Parts of the Construction Technology Project of Reinforced Concrete Bridge in Mostkovice
Keywords: most Mostkovice; technická zpráva; časový plán; finanční plán; rozpočet; plán nasazení hlavních mechanismů; situace stavby; zařízení staveniště; studie realizace; BOZP; technologický předpis; Bridge Mostkovice; technical report; time schedule; financial plan; budget; plan of using the main mechanisms; construction situation; site equipment; study of realization; health and safety at work; technological prescription